Experimental investigations of Jominy End Quench test using CuO nanofluids - M, Baskaran; KCK, Vijayakumar; Moorthy, Bharathiraja (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Nanofluids are the new class of quenching medium with colloidal suspensions of nanoparticles in base fluids, which improves the heat transfer characteristics. The present work has been focused on the quenching effect of mild steel and EN-8 steel with nanoparticles dispersed quenching medium. The different volume concentrations of nanofluids have been prepared by adding CuO nanoparticles with the average diameter of less than 50 nm in distilled water. Three volume concentrations (0.01%, 0.05% and 0.1%) of nanofluids have been prepared. EN8 and mild steel rod have machined as per Jominy end quench standard. The materials are heated up to 900â°C and the heated specimens are Jominy end quenched by using nanofluid. Heat transfer during the cooling has been recorded by interfacing the LabVIEW software, NI-DAQ kit and thermocouple. Then the hardness values are measured at different points on the work piece to examine the change in hardness of the quenched specimens. The result shows that, 0.05% volume concentration nanofluid exhibits a higher heat transfer rate; consequently the high hardness value has been achieved as compared with other specimens. The same effect has been observed with cooling curve, which was recorded by LabVIEW during the quenching process.